Ocean-lagoon water and plankton exchanges in a semi-closed pearl farming atoll lagoon (Ahe, Tuamotu archipelago, French Polynesia). (15th May 2017) - Pagano, M.; Rodier, M.; Guillaumot, C.; Thomas, Y.; Henry, K.; Andréfouët, S.
Abstract: In atoll lagoons, plankton richness is highly dependent on water exchange with the ocean through the atoll rim. However, the dynamics of the physical and biological fluxes at the lagoon-ocean interface remain poorly characterized. Here, we studied the combined effects of lagoon-ocean water exchanges and local environmental conditions on the phyto- and zooplankton abundance and community structure across the atoll lagoon rim of Ahe (Tuamotu Archipelago, French Polynesia). Plankton and environmental variables were monitored in May 2013 (i) at several stations inside and outside the lagoon and (ii) during time-series corresponding to ebb-flood tidal cycles in the two types of channels connecting the lagoon to the ocean: at the passage (300 m long and about 11 m deep) and in hoa (i.e reef-flat less than 50 cm depth). Our results highlight tidally-driven selective plankton exchanges between the lagoon and external ocean. Phytoplankton (chlorophyll-a) and zooplankton biomass were respectively 4 times and 7 times higher in the lagoon than at stations outside the atoll lagoon. Copepoda was the dominant zooplankton group at the oceanic station (>75% abundance) whereas meroplankton (with bivalve larvae most common) was dominant at the lagoon stations (54%), in the passage (55–82%) and in hoa (>80%). These differences between sites suggest a loss of bivalve larvae through export to the ocean and retention and/or increased production of copepods in the lagoon. The daily export of bivalve larvae represents a low percentage of the lagoon stock, in agreement with previously published larval dispersal numerical models. The retention of copepods could constitute a significant input of nutrients and organic matter (through excretion, feces release, decomposition, and remineralization) into the lagoon.